Equilibrium and kinetic study of novel methyltrimethoxysilane magnetic titanium dioxide nanocomposite for methylene blue adsorption from aqueous media. (20th April 2018) - Alizadeh Eslami, Parvin; Kamboh, Mohammad Afzal; Rashidi Nodeh, Hamid; Wan Ibrahim, Wan Aini
Abstract : Novel magnetic titanium dioxide nanoparticles decorated with methyltrimethoxysilane (Fe3 O4 @TiO2 ‐MTMOS) were successfully fabricated via a sol–gel method at room temperature. The synthesized material was characterized using Fourier transform infrared spectroscopy, X‐ray diffraction, scanning electron microscopy, energy‐dispersive X‐ray spectroscopy, thermogravimetric analysis and vibrating sample magnetometry. The removal efficiency of the adsorbent was evaluated through the adsorption of methylene blue (MB) dye from water samples. The adsorption isotherm and kinetics were evaluated using various models. The Langmuir model indicated a high adsorption capacity (11.5 mg g −1 ) of Fe3 O4 @TiO2 ‐MTMOS. The nanocomposite exhibited high removal efficiency (96%) and good regeneration (10 times) compared to Fe3 O4 and Fe3 O4 @TiO2 at pH = 9.0. Based on the adsorption mechanism, electrostatic interaction plays a main role in adsorption since MB dye is cationic in nature at pH = 9, whereas the adsorbent acquired an anionic nature. The newly synthesized Fe3 O4 @TiO2 ‐MTMOS can be used as a promising material for efficient removal of MB dye from aqueous media. Abstract : A newly synthesized magnetic nanocomposite (Fe3 O4 @TiO2 ‐MTMOS) as adsorbent was added into methylene blue (MB) dye solution and agitated for 5 min at pH = 9. Thereafter, residual concentration of MB was measured with UV–visible spectroscopy. High removal efficiency (96%) and good adsorption capacity (11.5 mg g ‐1 ) were obtained for MB in aqueous solution using the novel Fe3 O4 @TiO2 ‐MTMOS.